Evaluation of pancreatic cancer cell lines as a source of cancer stem cells (CSC) and their utilisation for assessing anti-CSC activities of KRAS binders - Teh, Yuan Han (2020)
Background: High incidence of recurrence has been recorded at 80% of pancreatic ductal adenocarcinoma (PDAC) cases, despite tumour resection and an adjuvant chemotherapy with gemcitabine are prescribed. Pancreatic cancer stem cells (CSCs) are believed to have initiated recurrent PDAC. Growing evidence indicates that these cells resist gemcitabine as a result of aberrant activation of KRAS, a molecular switch that regulates cancer-associated signalling pathways, including MAPK and PI3K-AKT. Vismodegib is the earliest known anti-pancreatic CSC agent, but its anti-CSC activity has been proven to be not translatable from bench to clinical settings. It is crucial to seek for an alternative to vismodegib. Patient-derived CSC culture is prevalently used for assessing potential anti-CSC agents in vitro, but patients’ biopsies may not be accessible to some researchers. Objectives: In the present study, PDAC cell lines were evaluated as a source of CSCs and they were utilised for assessing the anti-CSC potential of KRAS binders (DCAI and SRJ23) with their mechanisms of action being elucidated. Methods: Cell viability assays were performed to evaluate the cytotoxicity of gemcitabine, vismodegib, and KRAS binders in PDAC cell lines (BxPC-3, PANC-1, Capan-2, and MIA PaCa-2). Flow cytometry was employed to analyse the expression of pancreatic CSC surface markers (CD44, CD24, and CD133) on a singlecell basis. While tumoursphere-forming ability was investigated by culturing cells in serum-free and non-adherent conditions in vitro, the tumourigenicity of PDAC cells was assessed in immunocompromised mice. Molecular events were delineated by Western blotting and the presence of SOX2-expressing cells in tumour xenografts was evaluated by immunohistochemistry. Results: PANC-1 and Capan-2 cell lines showed exceptional resistance to gemcitabine with Capan-2 contains a notable number of putative CSCs co-expressing CD44, CD24, and CD133 (3.7% of the total population). These cells resisted the cytotoxicity of gemcitabine, but responded to vismodegib. Tumourspheres were found arising from BxPC-3 and Capan-2 cell lines only, but the latter had closer resemblance to CSCs based on their responsiveness to the inhibition induced by foetal bovine serum. The presence of tumoursphere-forming cells is consistent with BxPC-3 and Capan-2 cell lines being highly tumourigenic in immunocompromised mice. DCAI and SRJ23 abrogated the self-renewal of Capan-2 tumourspheres with the effect of SRJ23 being the greatest. DCAI and SRJ23 diminished SOX2 expression and signalling pathways that were essentially activated in Capan-2 tumourspheres. SOX2- expressing cells were found correspondingly present in xenografts of highly tumourigenic BxPC-3 and Capan-2 cell lines, except for PANC-1 xenografts, of which SOX2-expressing cells were present despite poorly tumourigenic. Conclusion: Capan-2 cell line contains a small subset of putative CSCs, suggesting that cancer cell line is a valid source of CSCs in the discovery of novel anti-CSC agents. This study provides first evidence of anti-CSC activity in DCAI and SRJ23, which is attained through inhibiting KRAS signalling. It is postulated that SRJ23 induces an additional inhibitory circuitry that involves protein phosphatase 2A, a dephosphorylating enzyme that inactivates NF-κB and WNT pathways, such that it emerges as a more promising candidate than DCAI in the future development of anti-CSC drug.